Annotated translation from english to spanish of the movie the beautiful truth. - Cedeño Carreño, María Augustina (2013)
The purpose of this study is to render and annotate the documentary movie The Beautiful Truth, by the Gerson Institute, into Spanish applying translation techniques learned during our academic program that support the whole translation process. This movie has to do with a nutritional program by Dr. Max Gerson and his natural therapy that, according to the Gerson Institute, many people have used to heal some chronic diseases in the USA. In order to develop this project, we have used some different methods. The method used on this research is mainly qualitative since we will go deeper into issues of interest by analyzing terms and phrases used in the translation process, as well as evaluating a logical Deduction and rhetorical of some of the lexical and grammatical structures and constructions. Of course, also by taking into account the numerous social and cultural benefits that we all may get from this translation. It is also descriptive and explanatory, as we illustrate the details about the whole translation process and the tools applied herein. It is also informative for the reason that one of the main ideas of this project, besides the translation process itself, is to contribute to the field of translation studies by providing the research community with thorough research work containing annotations in the scientific field.